Astrocytic GLUT1 deletion in adult mice enhances glucose metabolism and resilience to stroke - Laetitia Thieren; Henri S. Zanker; Jeanne Droux; Urvashi Dalvi; Matthias T. Wyss; Rebecca Waag; Pierre-Luc Germain; Lukas M. von Ziegler; Zoe J. Looser; Ladina Hösli; Luca Ravotto; E. Dale Abel; et al. (Nature Communications)
Abstract Brain activity relies on a steady supply of blood glucose. Astrocytes express glucose transporter 1 (GLUT1), considered their primary route for glucose uptake to sustain metabolic and antioxidant support for neurons. While GLUT1 deficiency causes severe developmental impairments, its role in adult astrocytes remains unclear. Here, we show that astrocytes and neurons tolerate the inducible, astrocyte-specific deletion of GLUT1 in adulthood. Sensorimotor and memory functions remain intact in male GLUT1 cKO mice, indicating that GLUT1 loss does not impair behavior. Despite GLUT1 loss, two-photon glucose sensor imaging reveals that astrocytes maintain normal resting glucose levels but exhibit a more than two-fold increase in glucose consumption, indicating enhanced metabolic activity. Notably, male GLUT1 cKO mice display reduced infarct volumes following stroke, suggesting a neuroprotective effect of increased astrocytic glucose metabolism. Our findings reveal metabolic adaptability in astrocytes, ensuring glucose uptake and neuronal support despite the absence of their primary transporter.